The Effect of RPM Coffee Roaster Machine on the Product Quality - Dedi Johanes Silaen; Achwil Putra Munir; Ainun Rohana (Universitas Sumatera Utara, 2014)
The RPM of coffee roaster mixer tool is needed to care. The machine RPM will affect the roasting quality. Various level of PRM were tested to know the quality of coffee produced. Research had been conducted at agricultural engineering laboratory, faculty Agricultural USU in July till October 2013 with using factorial randomized block design with one factor i.e 15, 25, 35, 45, and 55 revolution per minute. Parameters observed were organoleptic test, yield, process capacity and water content. The results showed that the RPM had highly significantly effect on the organoleptic test, yield, process capacity, and water content. Keywords:Ccoffee quality, coffee roaster machine, RPM test.